Kebijakan Hukum Pengelolaan Sampah di Desa Tarajusari Kabupaten Bandung - Rinaldi, Ferdian; Rinjani, Diliya Mariam; Nurfadila; Rashifah, Rini (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2025)
The village of Tarajusari faces complex problems, including pollution of the Citalugtug River due to waste accumulation, low productive utilization of organic waste, and limited land for waste management by the government through the design of a number of policies. The Community Service Program (PKM) of Langlangbuana University employs a participatory and educational approach to address these issues through four main activities. The implementation methods include educational flagship activities and the distribution of Black Soldier Fly (BSF) maggot larvae to three RW units in Dusun 1 through practical training and technology transfer in bioconversion, as well as observing the limitations of waste management land through documentation and interviews with residents. The solutions implemented include designing appropriate technology policies for Black Soldier Fly (BSF) maggot cultivation to convert organic waste into economically valuable products, community-based river cleanup efforts to address environmental pollution, and systematic documentation for advocacy to secure land for a waste management facility from the local government. The program's impacts include increased environmental awareness among the community, strengthened social bonds through community-based cleanup efforts, transfer of bioconversion technology skills to 10 participants, and economic empowerment through the reduction of 20-30 kg of organic waste per RW per month in the two participating RWs. The program's sustainability is supported by community commitment, collaboration with the Environmental Agency, and a continuous consultation system through contact with the PKM team.